Penerapan Model Pembelajaran Collaborative Learning dalam Meningkatkan Kemampuan Kognitif Anak Kelompok B TK Neo Genesis - Baene, Elfiras Handayani; Elizabeth Prima; Ni Made Ayu Suryaningsih (PRATAMA WIDYA : Jurnal Pendidikan Anak Usia Dini, 2025)
Cognitive ability is one of the important aspects that must be developed because thinking ability is the intelligence needed by children in order to develop knowledge about various things, both in solving problems and in understanding objects, events, and the environment. This study aims to evaluate the effectiveness of the collaborative learning model in enhancing the cognitive abilities of early childhood students in Group B at Neo Genesis Kindergarten. A varied and diverse learning model is one way to improve children's cognitive abilities, and this study was conducted to determine the improvement of cognitive abilities of Group B children at Neo Genesis Kindergarten through the application of collaborative learning models. The process of implementing research activities was carried out in 2 cycles, using observation sheets and documentation as data collection techniques. The results of the research that has been carried out can be seen in the increase in the percentage of children's completeness at the initial observation stage of 20%, in Cycle I the percentage increased to 45%, and in Cycle II the percentage of children's cognitive abilities increased again to 85%. In addition, the initial observation found several obstacles related to children's cognitive abilities, namely: children still have difficulty in classifying objects (based on colour, shape, and size), arranging and combining pictures, sorting numbers, and distinguishing the size of objects. Based on these data, it can be said that the application of collaborative learning models can improve the cognitive abilities of Group B children at Neo Genesis Kindergarten.